WhatsApp-Delivered Intervention for Continued Learning for Nurses in Pakistan During the COVID-19 Pandemic: Results of a Randomized-Controlled Trial - Jafree, Sara Rizvi; Zakar, Rubeena; Rafiq, Nasim; Javed, Ambreen; Durrani, Rana Rubab; Burhan, Syeda Khadija; Hasnain Nadir, Syed Mujtaba; Ali, Fatima; Shahid, Aimen; Momina, Ain ul; Wrona, Kamil J.; Mahmood, Qaisar Khalid; et al. (Frontiers in Public Health, 2022)
The COVID-19 pandemic has necessitated support for continued learning in frontline practitioners through online digital mediums that are convenient and fast to maintain physical distancing. Nurses are already neglected professionals for support in training for infection control, leadership and communication in Pakistan and other developing countries. For that reason, we aimed to deliver a WhatsApp-based intervention for continued learning in nurses who are currently working in both private and public sector. A twelve-week intervention was delivered to 208 nurses (102 in the control group and 106 in the intervention group) who had been employed in the clinical setting during data collection. The analysis reveals that nurses in the intervention group show significantly better results for learning in “infection prevention and control” and “leadership and communication”. Results of a content analysis based on participant’s feedback also confirm that the WhatsApp-based intervention is a valuable tool for education. This study highlights the effectiveness of online-based digital interventions as a convenient training tool for awareness and management of infectious diseases, leadership and communication during COVID-19 and beyond. Furthermore, this study emphasizes that group interventions with other healthcare practitioners and the role of on-going longer WhatsApp-based interventions can become integral tools to support continued learning and patient safety practices.